Contract No. 589393, Provision of Environmental Sensitivity Index Mapping Data - Universiti Malaysia Sarawak (Universiti Malaysia Sarawak, (UNIMAS), 1999)
Provision of Environmental Sensitivity Index Mapping Data Between Sarawak Shell Berhad/ Sabah Shell Petroleum Company Limited and Universiti Malaysia Sarawak